2018
DOI: 10.1002/14651858.cd011444.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine for preventing malaria in pregnant women

Abstract: BackgroundThe World Health Organization recommends intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine-pyrimethamine for malaria for all women who live in moderate to high malaria transmission areas in Africa. However, parasite resistance to sulfadoxine-pyrimethamine has been increasing steadily in some areas of the region. Moreover, HIV-infected women on cotrimoxazole prophylaxis cannot receive sulfadoxine-pyrimethamine because of potential drug interactions. Thus, there is an urgent need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…However, with resistance markers well above the threshold of 50% (for K540E) this cannot be supported. Although WHO still recommends IPTp with SP in areas with high level of resistance to SP, based on studies in Tanzania and Malawi [32], the current findings of high prevalence of SP resistance among the target population suggest that the efficacy of IPTp in this setting should continue to be monitored [33] and alternative drugs such as dihydroartemisinin-piperaquine, mefloquine or doxycycline may be worth considering [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with resistance markers well above the threshold of 50% (for K540E) this cannot be supported. Although WHO still recommends IPTp with SP in areas with high level of resistance to SP, based on studies in Tanzania and Malawi [32], the current findings of high prevalence of SP resistance among the target population suggest that the efficacy of IPTp in this setting should continue to be monitored [33] and alternative drugs such as dihydroartemisinin-piperaquine, mefloquine or doxycycline may be worth considering [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In the Democratic Republic of Congo (DRC) cases of malaria are rising, and the death toll is increasing [1]. In 2017 in DRC there was an estimated number of 25 million (15.7-36.8) cases of malaria and an estimated 46,800 (36,300) deaths. The majority of malaria cases in DRC are caused by Plasmodium falciparum, although Plasmodium ovale [2], Plasmodium malariae, and Plasmodium vivax are present among symptomatic cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The antimalarial drug mefloquine is currently used for both prevention (as a monotherapy) and treatment (either alone, or in combination with artesunate) of chloroquine-resistant Plasmodium falciparum malaria in humans [6][7][8]. It was found to substantially reduce the viral load of FIPV and feline calicivirus (FCV) at low concentrations in infected Crandell Rees feline kidney cells without cytotoxic effects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a large-scale study demonstrated the safety of chloroquine in pregnancy. 62 64 Pregnant women with SARS-CoV-2 infection are considered relatively high risk. The management strategy is shown below.…”
Section: Treatment and Managementmentioning
confidence: 99%